PREDICTION OF STRAND FEEDSTOCK MECHANICAL PROPERTIES WITH NEAR INFRARED SPECTROSCOPY - Neil J. Kohan; Brian K. Via; Steven E. Taylor (BioResources, 2012)
Wood strands either prepared in the laboratory or from a manufacturing plant were assessed for their ultimate tensile strength, tensile MOE, bending strength, and bending stiffness, and then near infrared spectroscopy was utilized for prediction. The ability to predict ultimate tensile strength and stiffness was generally weaker than bending strength and stiffness, perhaps due to the homogeneous distribution of stresses that occur within the strand during 3-point bending. Prediction of ultimate tensile strength and elasticity of plant based strands were generally weak due to imperfections in the strands that originate during biomass breakdown; however, for laboratory strands, prediction of tensile strength and stiffness was moderate/better. The modulus of elasticity for strands under bending exhibited the strongest correlation (R2 = 0.76). Principal component loadings were assessed, and it was found that the cellulose crystalline- and semi-crystalline-associated wavelengths were most important in predicting the stiffness for both tensile and bending forces; however, the influence of lignin-associated wavelengths increased in importance when predicting bending strength, and it was hypothesized that this was attributable to the plastic response of lignin above the proportional limit in the stress-to-strain curve. This study demonstrates the potential of near infrared spectroscopy to monitor the biomass quality prior to composite manufacture.